Comparison Of Serological Methods For The Detection Of Brucella Abortus Antibodies In Sera From Infected Bovines - Aher , A. S.; Londhe, S. P.; Mhase, P. P.; Bannalikar, A. S.; Dighe , V. D. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
The efficacy of rose Bengal plate test (RBPT) , standard tube agglutination test (STAT) and indirect enzyme linked immunosorbent assay (i-ELISA) in detection of bovine brucellosis was evaluated. The serum samples of 74 animals (68 cattle and 6 buffaloes )from different locations in Maharashtra were investigated for presence of Brucella antibodies by RBPT , STAT and i-ELISA. Overall observation of results of three serological tests employed in the present investigation for detection of bovine brucellosis suggests superiority of i-ELISA (56.75 %) over RBPT (54.05 %) and that of RBPT over STAT (47.29 %) in detecting the Brucella antibodies.